Perspectives on Schoenberg and Stravinsky - Boretz, Benjamin; Cone, Edward T. (Book collections on Project MUSE., 1968)
Perspectives on Schoenberg and Stravinsky is an analytical and historical study of the twentieth century's most influential figures, by Milton Babbitt, Arthur Berger, Edward T. Cone, Robert Craft, Claudio Spies, and others; with new bibliographic and discographic studies prepared especially for this revised edition. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.